2021
DOI: 10.1002/csr.2221
|View full text |Cite
|
Sign up to set email alerts
|

The influence of corporate social responsibility on students' emotional appeal in the HEIs: The mediating effect of reputation and corporate image

Abstract: The purpose of this paper is to study the influence of corporate social responsibility (CSR) over higher education institutions' (HEIs) students' emotional appeal and the effect of two mediating variables, corporate image, and reputation. A sample of 211 students surveyed was obtained, and the study was conducted using partial least squares path modeling (PLS‐SEM) technique. The results showed that emotional appeal is influenced by corporate reputation, corporate image, and CSR practices. These effects are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 136 publications
0
10
0
Order By: Relevance
“…We have chosen PLS-SEM to run our model because the model is formed by four composity type A [76]. In addition, PLS-SEM is an ideal technique when the relationships analysed are very complex, especially if there are mediating effects [77,78], it does not require a very large sample size and the data does not have to be strictly standardised [79].…”
Section: Discussionmentioning
confidence: 99%
“…We have chosen PLS-SEM to run our model because the model is formed by four composity type A [76]. In addition, PLS-SEM is an ideal technique when the relationships analysed are very complex, especially if there are mediating effects [77,78], it does not require a very large sample size and the data does not have to be strictly standardised [79].…”
Section: Discussionmentioning
confidence: 99%
“…Empirically, reputation was recognised as one of the mediators in predicting student loyalty in higher education. According to Aledo-Ruiz et al. (2021), reputation mediates the relationship between the corporate social responsibility of a higher education institution and the emotional appeal of its students.…”
Section: Hypotheses Development and Research Modelmentioning
confidence: 99%
“…Empirically, reputation was recognised as one of the mediators in predicting student loyalty in higher education. According to Aledo-Ruiz et al (2021), reputation mediates the relationship between the corporate social responsibility of a higher education institution and the emotional appeal of its students. In addition, Rasoolimanesh et al (2021) also reported that brand reputation of a higher education institution acts as a mediator between corporate social responsibility and the institution's brand loyalty.…”
Section: Mediating Effects Of Student Green Satisfaction and Institut...mentioning
confidence: 99%
“…There are many ways that business operation has affected the environment, society, and shareholders (Matten et al, 2020). Corporate reputation can be measured as the main intangible asset of a company which is halting from the companies past positive communications with shareholders (Aledo-Ruiz et al, 2022;Argenti & Druckenmiller, 2004). Beside reputation, corporate image is also an imperative intangible asset that represent a respected component in increasing the reputation in the management of universities (Maduro et al, 2018).…”
Section: Pr Profile Versus No Pr Profilementioning
confidence: 99%
“…Building a corporate image by communicating with various shareholders and stakeholders can be achieved through effective CSR activities. CSR activities are key devices to ensure proper shareholder communication, warrant better corporate transparency and a higher level of engagement with different shareholders (Aledo-Ruiz et al, 2022;Golob & Bartlett, 2007). Several researchers have discussed that positive image and satisfaction of customers are the results of CSR (Ali et al, 2020;Mulki & Jaramillo, 2011).…”
Section: Pr Profile Versus No Pr Profilementioning
confidence: 99%